Initial results of tests of depth markers as a surface diagnostic for fusion devices. (August 2017) - Kesler, L.A.; Sorbom, B.N.; Hartwig, Z.S.; Barnard, H.S.; Wright, G.M.; Whyte, D.G.
Highlights: AIMS diagnostic is undergoing development to enable high-Z erosion measurements. Technique uses an implanted depth marker as a reference to the surface for IBA. Also uses the ratio of two gamma yields to eliminate some parameters. Trials with a lithium depth marker were unsuccessful. Successfully measured depth of boron depth marker. Abstract: The Accelerator-Based In Situ Materials Surveillance (AIMS) diagnostic was developed to perform in situ ion beam analysis (IBA) on Alcator C-Mod in August 2012 to study divertor surfaces between shots. These results were limited to studying low-Z surface properties, because the Coulomb barrier precludes nuclear reactions between high-Z elements and the ∼1 MeV AIMS deuteron beam. In order to measure the high-Z erosion, a technique using deuteron-induced gamma emission and a low-Z depth marker is being developed. To determine the depth of the marker while eliminating some uncertainty due to beam and detector parameters, the energy dependence of the ratio of two gamma yields produced from the same depth marker will be used to determine the ion beam energy loss in the surface, and thus the thickness of the high-Z surface. This paper presents the results of initial trials of using an implanted depth marker layer with a deuteron beam and the method of ratios. First tests of a lithium depth marker proved unsuccessful due to the production of conflicting gamma peaks, among other issues. However, successful trials with a boron depth marker show that it is possible to measure the depth of the marker layer with the method of gamma yield ratios.